Limits on anomalous couplings from higgs boson production at the fermilab tevatron collider - De Campos, F. [UNESP]; Gonzalez-Garcia, M. C. [UNESP]; Novaes, Sérgio Ferraz [UNESP] (American Physical Society (APS), 1997)
We estimate the attainable limits on the coefficients of dimension-6 operators from the analysis of Higgs boson phenomenology, in the framework of a SU L(2) × U y(1) gauge-invariant effective Lagrangian. Our results, based on the data sample already collected by the collaborations at Fermilab Tevatron, show that the coefficients of Higgs-vector boson couplings can be determined with unprecedented accuracy. Assuming that the coefficients of all blind operators are of the same magnitude, we are also able to impose mere restrictive bounds on the anomalous vector-boson triple couplings than the present limit from double gauge boson production at the Tevatron collider.